Tuning the open circuit voltage by incorporating a diflurophenyl unit into a polymer backbone to achieve high efficiency polymer solar cells. Issue 3 (14th January 2021) - Hossain, Maimur; Afroz, Mohammad Adil; Garai, Rabindranath; Iyer, Parameswar Krishnan
Abstract : Fabrication of high performance polymer solar cells using a ternary polymer system modulates the morphology of the active layer, and significantly enhances the V oc, J sc, PCE and mobility values. Abstract : Two new random terpolymers, namely m1 PTB7-Th and m2 PTB7-Th, have been synthesized by incorporating the economical 2, 5-difluorobenzene (FBZ) molecule in the backbone of donor polymers for application in polymer solar cells (PSCs). Replacing 5 and 10 mole percentage of expensive monomer 3-fluorothieno[3, 4- b ]thiophene-2-carboxylate (FTT) in the well-explored donor polymer PTB7-Th with ∼100-time economical FBZ, new terpolymers, m1 PTB7-Th and m2 PTB7-Th, were obtained. These new terpolymers showed a deeper HOMO energy level, a comparable LUMO energy level with improved morphology and more planar molecular arrangements. These factors led to a remarkable enhancement in open circuit voltage ( V oc ) and short circuit current ( J sc ), which helped to achieve a higher power conversion efficiency (PCE) of 8.78% ( V oc = 0.852 V) with m1 PTB7-Th as compared to 7.87% for PTB7-Th ( V oc = 0.790 V). However, in case of m2 PTB7-Th, V oc reached up to 0.880 V with a lower PCE of 3.46% due to the lower range of solar absorbance and less fill factor (FF). The hole and electron mobility of the polymer active layers were estimated by the space charge limited current (SCLC) method. m1 PTB7-Th displayed improved hole and electron mobility values (2.68 × 10 −4 and 1.9 × 10 −4 cm 2 V −1 s −1, respectively) as compared to PTB7-Th- and m2 PTB7-Th-based devices since the polymer backbone had a lower dihedral angle and a superior blend morphology in thin films. The incorporation of the FBZ monomer into random copolymers has thus been shown to be a very effective method to synthesize cost-effective donor polymers to fabricate high performance PSCs with an improved V oc .